2005
DOI: 10.1089/ees.2005.22.221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fly Ash Transition Metal Content and Flue Gas HCl/SO2 Ratio on Mercury Speciation in Waste Combustion

Abstract: Understanding the transformation of mercury species (elemental and oxidized forms) in stationary combustion sources is of interest to both those responsible for developing control technologies and those responsible for setting regulations. Elemental mercury (Hg 0 ) poses a challenging flue gas control issue, and oxidized forms of mercury (Hg 2ϩ ) are of concern due to local deposition potential. In a previous study, mercury speciation, or more specifically oxidation of Hg 0 , was studied in simulated flue gase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 9 publications
2
70
2
Order By: Relevance
“…Such findings agree with results from Thorwarth et al 15 and Ghorishi et al, 25 but they do not necessarily mean that these oxides have no effects on mercury uptake or oxidation. They may inhibit mercury uptake or oxidation by consuming acid gases such as HCl, which is especially true for CaO.…”
Section: Mercury Speciation Tests With Synthetic Singlesupporting
confidence: 90%
See 1 more Smart Citation
“…Such findings agree with results from Thorwarth et al 15 and Ghorishi et al, 25 but they do not necessarily mean that these oxides have no effects on mercury uptake or oxidation. They may inhibit mercury uptake or oxidation by consuming acid gases such as HCl, which is especially true for CaO.…”
Section: Mercury Speciation Tests With Synthetic Singlesupporting
confidence: 90%
“…Some of the fly ash components promote oxidation of Hg°, whereas others do not. Ghorishi et al 25 studied the effects of synthetic model fly ash components on mercury speciation. The results showed that transition metal oxides, ferric oxide (Fe 2 O 3 ) and copper oxide (CuO), exhibited significant catalytic activity in oxidation of Hg°in the presence of hydrochloric acid (HCl) in simulated flue gas.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high chlorine partial pressure prevailing during waste combustion may cause the oxidation of mercury, and chloride mercury 13 species may be the major form in the cooling process of flue gas, as shown by Ghorishi et al. [23], Chen et al [24]. Lead, cadmium and copper show similar evaporation curves, with the principal volatilization between 650 and 1000 °C.…”
Section: Specific Behavior Of Pollutantsmentioning
confidence: 93%
“…3 In order to ensure the efficiency of mercury removal via WFGD units, there is a need for effective and regenerable mercury oxidation catalyst materials, and noble metals such as copper, silver, gold, and palladium are being investigated for this application. [4][5][6] Noble metals including platinum, gold, palladium, and copper have been investigated for incorporation in novel mercury removal sorbents, both for conventional coal-fired power plants and in the context ͑i.e., different temperature and pressure͒ of new integrated gasification combined-cycle ͑IGCC͒ power generation plants. 7,8 Despite the interest in using metals in mercury removal, very little research has been carried out to determine basic information about the binding of mercury to metal surfaces.…”
Section: Introductionmentioning
confidence: 99%